ANALISIS MUTU LAYANAN DAN TINGKAT KEPUASAN SISWA DALAM PEMBELAJARAN DARING SELAMA MASA PANDEMIC COVID 19 PADA SD KRISTEN SATYA WACANA SALATIGA: ANALISIS MUTU LAYANAN DAN TINGKAT KEPUASAN SISWA MODEL SERQUAL - Pujianto, Ari - (Satya Widya, 2021)
This study aims to review the factors of service quality at Satya Wacana Christian Elementary School Salatiga and see the components that affect student satisfaction levels during the Covid 19 pandemic. This research is a descriptive qualitative study to analyze service quality and student satisfaction levels using an analytical model. SERVQUAL service quality. The subjects of this study were teachers, students, and parents of students in the Satya Wacana Christian Elementary School, Salatiga. Data collection was carried out by means of documentation, namely by collecting school documents, interviews, and distributing questionnaires to school principals, teachers, students, and committees. school or student's parent representative. Through this research, it can be seen the factors that affect the quality of service and the level of student satisfaction at the Satya Wacana Christian Elementary School, Salatiga.